Implementing differentiated instruction based on learning styles to improve elementary students’ learning outcomes - Rheza Aulia Indira; Husni Wakhyudin; Kukuh Wahyudin Pratama (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2025)
The diversity of students' learning styles requires the application of adaptive learning strategies so that learning needs can be optimally met. This study aims to analyze students' learning styles, apply differentiated learning based on learning styles, and examine its impact on IPAS learning outcomes. The study uses a mixed method with a sequential exploratory design. Data were collected through learning style questionnaires, pretest, and posttest. The results showed that 41% of students had an auditory learning style, 33% had a visual learning style, and 26% had a kinesthetic learning style. Differentiated learning was implemented through the stages of diagnostic assessment, planning, implementation, and evaluation of learning. Analysis of learning outcomes showed an average score increase of 14.07, with significant paired samples test results (p < 0.0001). These findings indicate that differentiated learning based on learning styles has a positive effect on improving student learning outcomes. The implications of this study emphasize the importance of applying differentiated learning as an effective strategy to improve the quality of learning in elementary schools. Implementasi pembelajaran berdiferensiasi berdasarkan gaya belajar dalam meningkatkan hasil belajar siswa sekolah dasar Keberagaman gaya belajar peserta didik menuntut penerapan strategi pembelajaran yang adaptif agar kebutuhan belajar dapat terpenuhi secara optimal. Penelitian ini bertujuan untuk menganalisis gaya belajar peserta didik, menerapkan pembelajaran berdiferensiasi berdasarkan gaya belajar, serta mengkaji dampaknya terhadap hasil belajar IPAS. Penelitian menggunakan metode campuran dengan desain eksplorasi berurutan. Data dikumpulkan melalui angket gaya belajar, tes pretest, dan posttest. Hasil penelitian menunjukkan bahwa 41% peserta didik memiliki gaya belajar auditori, 33% visual, dan 26% kinestetik. Implementasi pembelajaran berdiferensiasi dilakukan melalui tahapan asesmen diagnostik, perencanaan, pelaksanaan, dan evaluasi pembelajaran. Analisis hasil belajar menunjukkan adanya peningkatan rata-rata skor sebesar 14,07, dengan hasil uji paired samples test yang signifikan (p < 0,0001). Temuan ini mengindikasikan bahwa pembelajaran berdiferensiasi berdasarkan gaya belajar berpengaruh positif terhadap peningkatan hasil belajar peserta didik. Implikasi penelitian ini menegaskan pentingnya penerapan pembelajaran berdiferensiasi sebagai strategi efektif untuk meningkatkan kualitas pembelajaran di sekolah dasar.